2014
DOI: 10.1007/s11356-014-3703-0
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary record of water column trophic conditions and sediment carbon fluxes in a tropical water reservoir (Valle de Bravo, Mexico)

Abstract: Valle de Bravo (VB) is the main water reservoir of the Cutzamala hydraulic system, which provides 40% of the drinking water consumed in the Mexico City Metropolitan Area and exhibits symptoms of eutrophication. Nutrient (C, N and P) concentrations were determined in two sediment cores to reconstruct the water column trophic evolution of the reservoir and C fluxes since its creation in 1947. Radiometric methods ((210)Pb and (137)Cs) were used to obtain sediment chronologies, using the presence of pre-reservoir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 46 publications
7
9
0
Order By: Relevance
“…Comparable patterns are found in nine Danish lakes (Fig. 4c), and although not corrected for sediment focusing, similar relative increases in OC burial have been reported from lakes in Mexico (threefold increase) and Germany (fourfold increase) in the modern period (Brothers et al 2013;Carnero-Bravo et al 2015). At Baldeggersee, Teranes and Bernasconi (2000), found an increase in OC burial rates, rising from 15 g C m 22 yr 21 pre-1960 to 103.5 g C m 22 yr 21 in 1995-1996.…”
Section: Quantifying Oc Burial Efficiencysupporting
confidence: 84%
“…Comparable patterns are found in nine Danish lakes (Fig. 4c), and although not corrected for sediment focusing, similar relative increases in OC burial have been reported from lakes in Mexico (threefold increase) and Germany (fourfold increase) in the modern period (Brothers et al 2013;Carnero-Bravo et al 2015). At Baldeggersee, Teranes and Bernasconi (2000), found an increase in OC burial rates, rising from 15 g C m 22 yr 21 pre-1960 to 103.5 g C m 22 yr 21 in 1995-1996.…”
Section: Quantifying Oc Burial Efficiencysupporting
confidence: 84%
“…In addtion, the influence of nutrient inputs on the enhancement of primary productivity needs to be taken into consideration for correctly evaluating the climate effects on primary productivity in reservoirs [ Carnero‐Bravo et al ., ]. In general, TP and TN concentrations show overall increasing trends toward to the surficial layers in the ZT and LA cores (Figure S6), whereas they are variable throughout the XFJ core.…”
Section: Discussionmentioning
confidence: 94%
“…However, their correlations with HI in the ZT, LA, and XFJ cores are weaker than the correlations of T 5 with HI (Table S2). Moreover, the TP and TN concentrations remained low level (mostly TP < 0.1 mg/g, TN < 0.4%) (Figure S6) during the past decades and are far smaller than those in sediments of other eutrophic reservoirs (TP: 0.3–0.83 mg/g, TN: 0.2–0.9% for Valle de Bravo Lake; TP: 0.55–0.99 mg/g for Qingcaosha reservoir) [ Carnero‐Bravo et al ., ; Jin et al ., ], suggesting the nutrient enrichment in ZT and LA cores either partially contributes to the productivity enhancement or is associated with climate change as the essential nutrient for algae growth. Thus, the nutrient input is not the key factor affecting the primary productivity in the three reservoirs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon burial rates have also been assessed in VB using sedimentary records and radiometric methods ( Carnero-Bravo et al, 2014 ). These authors found that C flux to the sediments increased significantly after 1991, rising from a previous average of 174 g C m −2 y −1 to an average of 250 g C m −2 y −1 ) between 1993 and 2005.…”
Section: Study Areamentioning
confidence: 99%